2010
DOI: 10.3109/10408444.2010.507182
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Butadiene: II. Genotoxicity profile

Abstract: 1,3-Butadiene’s (BD’s) major electrophilic metabolites 1,2-epoxy-3-butene (EB), 1,2-dihydroxy-3,4-epoxybutane (EBD), and 1,2,3,4-diepoxybutane (DEB) are responsible for both its mutagenicity and carcinogenicity. EB, EBD, and DEB are DNA reactive, forming a variety of adducts. All three metabolites are genotoxic in vitro and in vivo, with relative mutagenic potencies of DEB >> EB > EBD. DEB also effectively produces gene deletions and chromosome aberrations. BD’s greater mutagenici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 303 publications
1
38
0
Order By: Relevance
“…34,35 These results indicated that male reproductive genotoxicity of BD may still depend on the production of potent metabolites. 10,11 Our studies showed that DEB-induced long tails in the comet assay and the increase of MN frequencies in the CBMN assay, and the upregulation of γ-H2AX expression in Western blot in GC-2 cells further confirmed such damage. Previous studies in germ cells on the effects of DEB have been restricted to DNA damage.…”
Section: ■ Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…34,35 These results indicated that male reproductive genotoxicity of BD may still depend on the production of potent metabolites. 10,11 Our studies showed that DEB-induced long tails in the comet assay and the increase of MN frequencies in the CBMN assay, and the upregulation of γ-H2AX expression in Western blot in GC-2 cells further confirmed such damage. Previous studies in germ cells on the effects of DEB have been restricted to DNA damage.…”
Section: ■ Discussionsupporting
confidence: 79%
“…10 In addition to being carcinogenic in laboratory rodents and exposed workers, exposures to BD are associated with reproductive toxicity, 8 and there was evidence indicating that male reproductive genotoxicity of BD may still depend on the production of potent metabolites, corresponding to the results from carcinogenicity studies. 10,11 Previously in this study, we demonstrated the increased frequencies of MNi and nucleoplasmic bridges (NPBs) in BD-exposed workers. 12 In line with the epidemiological study, experimental studies have shown DEB to be a potent inducer of chromosome aberrations and MNi in germinal cells in vivo and in vitro.…”
Section: ■ Introductionmentioning
confidence: 98%
See 3 more Smart Citations